Religião e mal-estar a partir do pensamento de Freud e de Tillich : interpelações e apontamentos na atualização do diálogo entre teologia e a psicanálise - Miranda, Claudio Nilcon Leites (2023)
At the centre of interest of this research is the malaise and religion theme. The human and social sciences note a malaise that exists as a condition in the existence of the contemporary human being. The subject that the Christian theology has always recognised as a consequence of “fallen existence” of the human being is now recognised by the philosophy of existence as an existential condition and, as such, insuperable. The agreement about the presence of a “being ill” in the existence, however, does not mean an agreement about the origin of this evil. The Freudian psychoanalysis has been considered a privileged lens in the reading and analysis of such condition, especially in due to its special discovery: the unconsciousness. For this reason, it has been put, in this research, as a companion of dialogue and debate with the theology. The research has been mediated by the ideas of Sigmund Freud, from the psychoanalytic point of view, and Paul Tillich, from the theological point of view. Both authors proved to be fundamental for the analysis of the theme: Freud, due to his research on psychology of the depth, Tillich, due to his special philosophical and theological sensitivity, which enabled him to have a deep perception of the human condition. Part I of the research was dedicated to preliminary questions, where a brief biography of the intellectual itinerary of both authors is offered; also, the use made of the terms malaise and religion throughout the research was delimited. In Part II we tried to give the floor to Freud, with the intention of getting to know the concepts of malaise and religion from the author's point of view, having the lens of psychoanalytic theory as a hermeneutic principle. Part III was reserved for the same route, considering the concepts from Paul Tillich's point of view, reflected from philosophy and theology, having as hermeneutic principle his “Correlation Theory”. In parts II and III, the text keeps being more synthetic than analytical, reserving a more critical procedure in parts IV and V. In Part IV, we sought to update the debate on theology and psychoanalysis, regarding the subject of malaise and religion, as well as considering the bases on which this dialogue can take place. Finally, in Part V, some questions and notes are made for the future of this dialogue. In this sense, we suggest the possibility of a new field of research that encompasses both knowledge – theology and psychoanalysis –, considering that the breadth of the theme requires an approach that should be multi/inter/trans/disciplinary